Src-homology protein tyrosine phosphatase-1 agonist, SC-43, reduces liver fibrosis - Tung-Hung Su; Chung-Wai Shiau; Ping Jao; Nian-Jie Yang; Wei-Tien Tai; Chun-Jen Liu; Tai-Chung Tseng; Hung-Chih Yang; Chen-Hua Liu; Kai-Wen Huang; Ting-Chen Hu; Yu-Jen Huang; et al. (Scientific Reports, 2017)
Abstract This study aimed to investigate the role of src-homology protein tyrosine phosphatase-1 (SHP-1)–signal transducer and activator of transcription 3 (STAT3) pathway in liver fibrogenesis and the anti-fibrotic effect of SHP-1 agonist. The antifibrotic activity of SC-43, a sorafenib derivative with an enhanced SHP-1 activity, was evaluated in two fibrosis mouse models by carbon tetrachloride induction and bile duct ligation. Rat, human, and primary mouse hepatic stellate cells (HSCs) were used for mechanistic investigations. The results showed that SHP-1 protein primarily localized in fibrotic areas of human and mouse livers. SC-43 treatment reduced the activated HSCs and thus effectively prevented and regressed liver fibrosis in both fibrosis mouse models and improved mouse survival. In vitro studies revealed that SC-43 promoted HSC apoptosis, increased the SHP-1 activity and inhibited phospho-STAT3. The enhanced SHP-1 activity in HSCs significantly inhibited HSC proliferation, whereas SHP-1 inhibition rescued SC-43-induced HSC apoptosis. Furthermore, SC-43 interacted with the N-SH2 domain of SHP-1 to enhance the activity of SHP-1 as its antifibrotic mechanism. In conclusion, the SHP-1–STAT3 pathway is crucial in fibrogenesis. SC-43 significantly ameliorates liver fibrosis through SHP-1 upregulation. A SHP-1-targeted antifibrotic therapy may represent a druggable strategy for antifibrotic drug discovery.